The Potential of "Wii Fit Free Jogging" as an Exercise Test - Hussey, Juliette; Forde, Cuisle; Gormley, John (Games for Health Journal, 2014)
Objective: The aim of this study was to investigate the potential use of "Wii Fit Free jogging" (Nintendo, Kyoto, Japan) as a tool to estimate aerobic fitness in healthy young adults. It was hypothesized that virtual distance achieved, an outcome reported by the "Wii Fit Free Jogging" game, may be used to estimate aerobic fitness. Materials and Methods: Two exercise tests using "Wii Fit Free Jogging " were developed: The Wii Jogging Test and the Wii Step Test. For the Wii Jogging Test participants were required to jog on the spot with the aim of achieving the highest virtual distance possible in a given time. For the Wii Step Test participants had the same aim but were required to step up and down a 30cm step. The construct and criterion validities of these tests were examined in two separate studies. Results were compared with maximal oxygen consumption measured using and Oxycon Mobile indirect calorimeter (Jaeger, Viasys Healthcare, Hoechberg, Germany) and a Polar heart rate monitor (Polar Electro Oy, Kempele, Finland). Results: There was no difference between the highest oxygen consumption reached during the Wii Step Test and VO2max (P=0.101). In regression analysis virtual distance results from neither the Wii jogging Test nor the Wii Step Test contributed to the prediction of VO2max (P=0.235 and P=0.396, respectively). Conclusions: In its current form, Wii Fit Free Jogging is not suitable for use as an exercise test. Although it elicited near maximal exertion, there was no valid method of estimating aerobic fitness from virtual distance results.
PUBLISHED